Effects of different squat angles and surface stability on lower limb muscle activation: A surface electromyography study - Purnomo, Ardhi Mardiyanto Indra; Kiartivich, Suparata; Firdaus, Mokhammad (UIR Press, 2026)
Background: The squat is a fundamental lower-body exercise that activates key muscles, including the rectus femoris, vastus medialis oblique, biceps femoris, and semitendinosus. Variations in angle and stability may influence muscle activation, though evidence on their combined effects remains limited. Surface electromyography (sEMG) is a reliable method for assessing these responses for training and injury prevention. Objectives: This study aimed to investigate the effect of squat angle and the use of a balance dome on lower limb muscle activation using sEMG. Methods: A within-subject experimental design with 10 participants examined lower limb muscle activation using surface electromyography (sEMG) during squats at 90° and 120° under stable and unstable conditions. Signals were processed via RMS and MVC normalisation. A two-way repeated-measures ANOVA assessed main and interaction effects, reporting F-values, degrees of freedom (df), and effect sizes (η²p). Bonferroni-adjusted post hoc tests were applied, with p < 0.05 considered significant. Results: A repeated-measures design revealed muscle-specific differences in activation across conditions. Quadriceps activation was higher at 90°, while hamstrings were more responsive to instability. Significant effects were observed for VMO (F(1,9) = 41.201, p < 0.01, η²p = 0.370) and biceps femoris (F(1,9) = 36.720, p < 0.01, η²= 0.517). Overall, squat angle had a stronger influence than stability. Conclusion: Preliminary findings indicate squat muscle activation is muscle-specific and condition-dependent. Quadriceps respond to angle and stability, while hamstrings act as stabilisers. Instability alters neuromuscular strategy. Findings should be interpreted cautiously due to the small sample size and limitations of the EMG.